Urinary podocyte-associated molecules and albuminuria in hypertension. Issue 8 (August 2018) - Perez-Hernandez, Javier; Olivares, Maria D.; Solaz, Elena; Martinez, Fernando; Martínez-Hervas, Sergio; Pichler, Gernot; Chaves, Felipe J.; Redon, Josep; Cortes, Raquel
Abstract : Objective: Hypertension-induced podocyte damage and the relationship with UAE is analyzed in diabetic and nondiabetic participants. Patients and methods: Sixty-four hypertensive patients, 30 diabetics, with glomerular filtration rate (eGFR) greater than 60 ml/min per 1.73 m 2 were included. Urinary albumin excretion was measured in morning urine using a nephelometric immunoassay and expressed as albumin/creatinine ratio. Urinary pellets were obtained from fresh urine and mRNA was assessed by real-time quantitative PCR. Likewise, protein podocyte-specific molecules were measured by western blot using specific antibodies. Results: Fourteen nondiabetics and 20 diabetics had increased UAE greater than 30 mg/g. In individuals with increased EUA, the mRNA expression of nephrin and CD2AP was low in diabetics, whereas only nephrin mRNA in nondiabetics. No differences were observed in podocalyxin and aquaporin-1 mRNA levels. Concerning the protein values, in both nondiabetic and diabetic patients, nephrin, CD2AP and podocalyxin were increased in patients with increased UAE, with no differences in aquaporin-1. A significant positive relationship was observed between log UAE and nephrin protein values, and an inverse association observed with mRNA. Conclusion: Hypertensive patients who had elevated UAE showed increased urinary excretion of podocyte-specific proteins coupled with a phenotype of decreased mRNA expression. The phenotype of podocyte-specific mRNA and the increment of nephrin can be used as a valuable marker of early glomerular injury.